Process and product characteristics for carbonization of liquid–solid mixtures from coal liquefaction. Issue 3 (June 2018) - You, Quan; Wu, Shiyong; Wu, Youqing; Huang, Sheng; Gao, Jinsheng; Shang, Jianxuan; Min, Xiaojian; Zheng, Hua'an
Abstract: In this paper, a carbonization process for valid liquid–solid separation and upgrading of coal liquefaction residues was proposed and practiced using batch-type devices. The effect of carbonization times and temperatures on the efficiency of liquid–solid separation and product distributions were investigated using self-prepared liquid–solid mixtures (CSMs) from direct coal liquefaction. It was suggested that the carbonization temperature and blowing gases were essential to the efficient liquid–solid separation in this process, and the carbonization process was characterized by the efficient liquid–solid separation. The n -hexane soluble fractions (HS) can be largely separated from CLMs. It was remarkable that over 0.06–1.50% of HSs can be additionally produced at the higher temperatures (430 °C–500 °C). On the other hand, the obtained semi-cokes (SCs) were mainly characterized as a rich carbon-containing material with high heating values. Some of the SCs were characterized by the better caking property with the caking index ( G ) from 68.5 to 75.2. In addition, it was proved that the caking property of SCs is directly affected by the asphaltenes (ASs) instead of pre-asphaltenes (PAs). Highlights: Comprehensive investigations on the effects of carbonization temperature and time on the products distribution. A feasible separation method for the liquid-solid mixtures derived from direct coal liquefaction. Over 0.06–1.50% of extra produced light fractions (HSs). Caking property of obtained semi-cokes (SC) is predominately influenced by the asphaltenes rather than pre-asphaltenes.